Effect of thermoelectric modules with different characteristics on the performance of thermoelectric generators inserted in the central flow region with porous foam copper. (1st December 2022) - Li, Yanzhe; Wang, Shixue; Zhao, Yulong; Yue, Like
Highlights: Central flow heat transfer enhancement with porous foam copper inserted in the TEG has been studied by experiment. The effect of different PPI of the porous foam copper on the TEG has been analyzed. The effect of different volume ratios of the porous foam copper on the TEG has been analyzed. TEGCP is used to analyze the performance of enhancing heat transfer in the central flow region of the TEG. Abstract: The recovery and utilization of waste heat by thermoelectric power generation technology can effectively improve energy utilization efficiency and solve the problem of environmental pollution and resource shortage. In this study, a thermoelectric power generation system is established to recover and utilize high temperature waste heat for thermoelectric power generation. In order to improve the conversion efficiency of thermoelectric generator, porous foam copper is inserted into the central flow region of thermoelectric generator to enhance the heat transfer effect at the hot side, and the thermoelectric generator Comprehensive Performance (TEGCP) as a evaluation standard is used to analyze the performance of thermoelectric generator under the porous foam copper central flow region inserted method. The results show that the thermoelectric module with low thermal conductivity and high electrical conductivity can play a better performance in the thermoelectric generator. Moreover, the heat exchange capability of the thermoelectric generator heat exchanger can be significantly increased when the porous foam copper is inserted in the central flow region. Compared with an insert-free thermoelectric generator, the output power of the thermoelectric generator using porous foam copper with high pore density and high volume ratio is increased by 2.3 times. Through the TEGCP that, the use of 15 mm thickness (75 % volume ratio), 20PPI porous foam copper with the module KTGM161-18 and the central flow region inserted method has the best influence of the thermoelectric generator.